2016
DOI: 10.1177/0095798416683170
|View full text |Cite
|
Sign up to set email alerts
|

Academic Identity: A Longitudinal Investigation of African American Adolescents’ Academic Persistence

Abstract: Adolescence is a vulnerable period for the development of academic identification and academic persistence, particularly among African American adolescents. The present study investigated how cultural assets (i.e., private regard and racial centrality) and academic assets (i.e., academic curiosity and academic self-esteem) influence African American adolescent boys' (n = 109) and girls' (n = 153) academic persistence over time. Additionally, we explored whether oppositional academic identity mediated the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
(96 reference statements)
1
18
0
Order By: Relevance
“…Finally, there is a dearth of research examining contextual variation in the associations among racial discrimination, racial identity, and academic engagement, specifically the variation between youth in predominately Black and predominately White school settings. As such, this study tested contentions from prior scholarship linking racial centrality and public regard to positive academic engagement for Black adolescents, especially in predominately White schools, where they may routinely experience token status and challenging racial climates (Butler-Barnes, Varner, Williams, & Sellers, 2017).…”
Section: Study Aimsmentioning
confidence: 99%
“…Finally, there is a dearth of research examining contextual variation in the associations among racial discrimination, racial identity, and academic engagement, specifically the variation between youth in predominately Black and predominately White school settings. As such, this study tested contentions from prior scholarship linking racial centrality and public regard to positive academic engagement for Black adolescents, especially in predominately White schools, where they may routinely experience token status and challenging racial climates (Butler-Barnes, Varner, Williams, & Sellers, 2017).…”
Section: Study Aimsmentioning
confidence: 99%
“…Adolescent Black girls with a strong sense of self are determined to stay focused in school and maintain their grades even through adversity (Morris, 2007; Pearson, 2008). Black girls who academically persist in school often report having high grades and are academically curious (Butler-Barnes et al, 2017). Interestingly, participation in physical activity has been shown to increase persistence, alleviate boredom, and increase concentration leading to higher academic performance for Black girls (Shen, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Black girls’ aspirations may help develop future academic outcomes (Honora, 2002). High academic aspirations enable Black girls to persist academically and overcome difficulties (Butler-Barnes et al, 2017; Neal-Jackson, 2018). Black girls maintain that hard work leads to academic success and a way to reverse negative socioeconomic status (Archer-Banks & Behar-Horenstein, 2012; Evans-Winters, 2005; Neal-Jackson, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational expectancy, which is how an individual identifies with their academics and their views regarding their academic ability, can help shape a person's beliefs regarding their academic self-concept. For Black males, the development of a negative academic self-concept and academic disidentification is often linked with experiences of discrimination and negative messages received in the academic setting (Butler-Barnes et al, 2016). Noguera (2003) reported that classroom settings influence how Black males perceive and understand themselves within the academic environment.…”
Section: Black Males' Educational Expectancymentioning
confidence: 99%